2018
DOI: 10.1182/blood-2017-06-789552
|View full text |Cite
|
Sign up to set email alerts
|

Unopposed IL-18 signaling leads to severe TLR9-induced macrophage activation syndrome in mice

Abstract: The term macrophage activation syndrome (MAS) defines a severe, potentially fatal disorder characterized by overwhelming inflammation and multiorgan involvement. Interleukin-18 (IL-18) is a proinflammatory cytokine belonging to the IL-1 family, the activity of which is regulated by its endogenous inhibitor IL-18 binding protein (IL-18BP). Elevated IL-18 levels have been reported in patients with MAS. Herein, we show that on repeated toll-like receptor 9 (TLR9) stimulation with unmethylated cytosine guanine din… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 24 publications
(30 reference statements)
12
91
0
1
Order By: Relevance
“…Recent studies revealed some biomarkers including IL-18, CXCL9, neopterin and soluble tumor necrosis factor receptor type II might be useful for the prediction of the development of MAS and the diagnosis of the transition from active phase of s-JIA to MAS [14][15][16][17][18][19][20][21]. Recent studies revealed that high levels of free IL-18 (that is, IL-18 not bound to IL-18 binding protein) increases the risk of developing MAS [15,22]. We previously reported that serum IL-18 levels were markedly elevated in patients with MAS while treated with TCZ and their levels positively correlated with the measures of disease activity [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed some biomarkers including IL-18, CXCL9, neopterin and soluble tumor necrosis factor receptor type II might be useful for the prediction of the development of MAS and the diagnosis of the transition from active phase of s-JIA to MAS [14][15][16][17][18][19][20][21]. Recent studies revealed that high levels of free IL-18 (that is, IL-18 not bound to IL-18 binding protein) increases the risk of developing MAS [15,22]. We previously reported that serum IL-18 levels were markedly elevated in patients with MAS while treated with TCZ and their levels positively correlated with the measures of disease activity [3].…”
Section: Discussionmentioning
confidence: 99%
“…Patients demonstrate chronically and extremely high levels of serum IL-18, as well as evidence for IFN-γ activity during flares (14). Highly elevated serum IL-18 levels emerged as risk factors for developing macrophage activation syndrome (MAS) and have been associated with the development of MAS in systemic juvenile idiopathic arthritis and adult-onset Still's disease (15,16). The disease-causing NLRC4 mutations have associated the NLRC4 inflammasome but not the other inflammasomes with very high IL-18 activation (15).…”
Section: Funding the Intramural Research Program Of The Nih Niaid mentioning
confidence: 99%
“…Furthermore, with several animal models, they demonstrate that IL-18 is not just a biomarker but rather a driver of inflammation and potential therapeutic target in some patients with MAS. 1,2 Hemophagocytic lymphohistiocytosis (HLH) is a syndrome driven by a range of inherited and acquired factors that lead to extreme inflammation. In patients with familial HLH (fHLH) resulting from severe defects in genes regulating cytotoxic granule release (PRF1, UNC13D, STX11, and STXBP2), failure to clear antigen leads to acute hyperimmune activation with progressive organ damage and death unless inflammation is controlled with aggressive immune suppression.…”
Section: Texasmentioning
confidence: 99%